Practices of social justice-oriented teacher education: a review of the literature - Hosseini, Nina; Leijgraaf, Monique; Gaikhorst, Lisa; Volman, Monique (Frontiers in Education, 2024)
Social justice-oriented teacher education has emerged as a critical area of inquiry within the field of education. Drawing on 60 empirical papers, this scoping review examines what shared principles can be distinguished in how teacher educators shape their social justice-oriented teacher education practices. Social justice-oriented teacher education practices are characterized by their focus on identifying structural inequities and disrupting unjust hierarchies, for example, in which knowledge and perspectives are undervalued or marginalized. Social justice-oriented teacher education actively engages with the context and communities in which teaching takes place. In their curriculum and pedagogical approach, teacher educators pay attention to unequal power relations and centralizing marginalized perspectives. The papers included in this review further emphasize the importance of critical reflection and enacting shared principles in ways that fit the local context and power dynamics.